The Impact of m6A RNA Modification in Therapy Resistance of Cancer: Implication in Chemotherapy, Radiotherapy, and Immunotherapy - Shriwas, Omprakash; Mohapatra, Pallavi; Mohanty, Sibasish; Dash, Rupesh (Frontiers in Oncology, 2021)
m6A RNA methylation, which serves as a critical regulator of transcript expression, has gathered tremendous scientific interest in recent years. From RNA processing to nuclear export, RNA translation to decay, m6A modification has been studied to affect various aspects of RNA metabolism and it is now considered as one of the most abundant epitranscriptomic modification. RNA methyltransferases (writer), m6A-binding proteins (readers) and demethylases (erasers) proteins are frequently upregulated in several neoplasms thereby regulating oncoprotein expression, augmenting tumor initiation, enhancing cancer cell proliferation, progression and metastasis. Though the potential role of m6A methylation in growth and proliferation of cancer cells has been well documented, but it’s potential role in development of therapy resistance in cancer is not clear. In this review, we focus on m6A-associated regulation, mechanisms and functions in acquired chemoresistance, radioresistance and resistance to immunotherapy in cancer.